Дослідження розподілів контактного тиску і напружено-деформованого стану елементів конструкцій торсіонних валів підвіски бойових броньованих машин - Ткачук, Микола Миколайович; Зінченко, Олена Іванівна; Грабовський, Андрій Володимирович; Ткачук, Микола Анатолійович; Льозний, Олег Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У роботі показано необхідність урахування чинника сумісного взаємовпливу контактної взаємодії та пластичного деформування у зоні головки торсіонного вала на міцність торсіонних валів підвіски бойових броньованих машин задля досягнення поліпшення технічних рішень елементів систем підресорювання легкоброньованих машин, та, відповідно, тактико-технічних характеристик рухливості. Проведений аналіз впливу варіювання властивостей матеріалів та форми контактуючих поверхонь на контактну взаємодію та напружено-деформований стан торсіонних валів.

The work demonstrates the need in accounting for the factor of the mutual influence of contact interaction and plastic deformation in the area of the head of the torsion shaft on the strength of the torsion shafts of the suspension of armored combat vehicles in order to achieve improvements in the technical solutions for the elements of the suspension systems of light-armored vehicles, and, accordingly, the tactical and technical characteristics of mobility. An analysis of the effect of varying the properties of materials and the shape of the contacting surfaces on the contact interaction and the stress-strain state of torsion shafts was carried out. In the presence of limitations on the dimensions of the head of the torsion shaft of the suspension systems of lightly armored vehicles, one of the important solutions is the modification of the working surfaces of the spline connection, which makes it possible to reduce the level of contact pressure in the spline coupling on the head of the torsion shaft.
Research of the distributions of contact pressure and the stress-deformed state of the elements of the structures of the torsion shafts of the suspension of armored vehicles
Keywords: легка броньована машина; торсіонний вал; тактико-технічні характеристики; напружено-деформований стан; головка торсіонного вала; стебло торсіонного вала; галтельний перехід; контактний тиск; пружно-пластичне деформування; шліцьова втулка; light armored vehicle; torsion shaft; tactical and technical characteristics; stressed-deformed state; torsion shaft head; torsion shaft stem; pinion transition; contact pressure; elastic-plastic deformation; splined sleeve